2013
DOI: 10.1016/j.apnu.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Anhedonia: A Concept Analysis

Abstract: Anhedonia presents itself in a myriad of disease processes. To further develop our understanding of anhedonia and effective ways to manage it, the concept requires clear boundaries. This paper critically examined the current scientific literature and conducted a concept analysis of anhedonia to provide a more accurate and lucid understanding the concept. As part of the concept analysis, this paper also provides model, borderline, related, and contrary examples of anhedonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 96 publications
0
57
0
Order By: Relevance
“…Several authors advise to bear in mind that the symptom of anhedonia occurs on a continuum of hedonic tone and advise to measure it in a dimensional manner (Ho & Sommers, 2013). Therefore, we used the French version (Loas et al, 2009) really look forward to it").…”
Section: Behavioral and Self-report Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors advise to bear in mind that the symptom of anhedonia occurs on a continuum of hedonic tone and advise to measure it in a dimensional manner (Ho & Sommers, 2013). Therefore, we used the French version (Loas et al, 2009) really look forward to it").…”
Section: Behavioral and Self-report Measuresmentioning
confidence: 99%
“…However, only a few studies have investigated the specific symptom of anhedonia, which is supposed to be associated with this altered reward processing. Moreover, even though it has been suggested that anhedonia should be considered in a dimensional perspective (Ho & Sommers, 2013), even less studies have measured this symptom on a continuum. We believe that symptom-focused transdiagnostic studies are necessary and that an in-depth investigation of the specific role of anhedonia in reduced reward responsiveness is important and overdue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression, according to the diagnostic criteria of DSM‐5, takes into account also lack of pleasure, “anhedonia,” as a feature of the diagnosis . Depressed patients do not always show anhedonia, and conversely, anhedonic patients may show a specific alteration in experiencing the pleasure that is independent of their sadness status . Nevertheless, anhedonia, unlike depression, is rarely taken into account when we approach a patient with a known GI disease.…”
Section: Discussionmentioning
confidence: 99%
“…9 Depressed patients do not always show anhedonia, and conversely, anhedonic patients may show a specific alteration in experiencing the pleasure that is independent of their sadness status. [27][28][29] Nevertheless, anhedonia, unlike depression, is rarely taken into account when we approach a patient with a known GI disease. Furthermore, it has been shown that anhedonia is particularly difficult to treat, and its presence predicts a poor treatment response to classical antidepressant therapy.…”
Section: In Recent Years a Relationship Between Diseases And Mood DImentioning
confidence: 99%